Prevalence of alcoholic beverages among Brazilian adolescents aged 13 to 18 years and its association with demographic and behavioral characteristics (Research, Society and Development, 2018)
Generally, the phase of adolescence is characterized by physical, mental and social changes and such changes cause adolescents to behave differently than usual and, in an attempt to self-assert, adolescents become more susceptible to risky behaviors, including use of alcoholic beverages. In this sense, the objective of the present study is to estimate the prevalence of alcohol consumption among Brazilian adolescents in the year 2015 and possible demographic and behavioral factors associated with this prevalence. To do so, the results of the National School Health Survey for the year 2015 were used as the data base, where the bivariate analysis of the independent variables pertinent to the study was performed initially. Subsequently, the Poisson regression was applied in order to find the association between the independent variables and the outcome variable. The study concludes that there is a higher prevalence for the use of alcoholic beverages among adolescents who declared themselves to be pardos, with ages between 15 and 16, residents of the Southeast region. In addition, no differentiation was found in the prevalence of drink use by genre. Regarding the behavioral variables, there was a higher prevalence of drinking among adolescents who had friendships with people who also used beverages, among adolescents who used other types of drugs and who were already involved in fights with firearms.